'A life path different from one of labour in the Gulf': Ongoing mobility among Nepali labour migrants in Qatar and their families. (5th August 2022) - Limbu, Amrita
Abstract: Labour migration is commonly attached to the idea of a 'better' future for the migrants and their families, but there is less emphasis on how this does not materialize for many labour migrants. Drawing on ethnographic fieldwork among Nepalis working in Qatar and select families in Nepal, this article focuses on the intergenerational migration cycle or migration as open‐ended and ongoing across generations. While the Gulf migration scholarship has mostly concentrated on low‐skilled workers, I draw on the cases of migrants across different skill/income levels to show how the migrants' and/or families' desires for 'ongoing mobility' to the Gulf or the West panned out differently. I argue that despite wanting a different and better life path for the future generation, one unlike theirs of labour in the Gulf, many Gulf migrants are unable to meet these familial expectations; rather, migration histories repeat in a continual quest to overcome economic constraints.